Schizophrenia in contemporary Cinema: film and clinical analysis - Joana de Sá Osório Dias Maia (2021)
Background and Objectives: Cinema has always reflected the "human being", and commonly creators focus on one of its mysteries: Mental Health. Schizophrenia is an intriguing disease with several aspects still unknown and frequently showcased in cinema. The representation of this pathology in contemporary films is the main focus of this article with three distinct objectives to analyze: the accuracy of the representation of signs and symptoms of schizophrenia, the portrayal of its treatment and the influence films have on family and friends of patients. Methods: Articles were electronically searched in PubMed and Web of Science. Articles since 1985 written in English which focused on English-language films were analyzed. Three films were watched: A Beautiful Mind, The Soloist and Words on Bathroom Walls. Additionally, films reviews were also included. Results: Results suggest that the representation of symptoms is inaccurate and overrepresents visual aspects of the disease. Treatment is often described as aversive and intolerable. Nevertheless, there seems to be agreement between the authors' proposal and the current scientific knowledge about the importance of friends and family intervention for better outcomes. Conclusions: Cinema does not always properly translate the psychopathological phenomena that occur in schizophrenia which can misguide the audience. The magical and fanciful character that filmmakers express can further alienate the patient, reducing understanding of the disease and increasing the stigma. Closer collaboration should exist between filmmakers and psychiatrists towards a better representation of patients with schizophrenia, their treatment and all aspects which promote acceptance and inclusion.